Peran Kepala Sekolah Visioner Dalam Membentuk Karakter Peserta Didik di Era Transformasi Teknologi - Anis Faizatul Imamah Imamah; Sarana sarana; Mujiati; Sulistyo Wulandari (Pascasarjana Manajemen Pendidikan Universitas Gresik, 2025)
This study aims to analyze the role of visionary leadership of school principals in shaping students' character in the era of technological transformation. Using a qualitative approach and literature study methods, this study examines various relevant sources to identify strategies and challenges faced by school principals in integrating character values ​​with the demands of the digital era. The results show that visionary principals act as agents of change, innovators, and role models in building a character-based school culture. They not only formulate a clear, future-oriented vision but also communicate it effectively, improve teacher competency, encourage technological innovation, and build collaboration with all stakeholders. However, the implementation of visionary leadership still faces obstacles such as limited resources, low technological readiness, and resistance to change. This study concludes that visionary leadership is key to creating an adaptive, innovative, and character-based educational environment in the era of digital transformation.